Management of mixed oak-pine forests under climate - Gutsch, M.; Lasch, P.; Suckow, F.; Reyer, C. (Forest Systems, 2011)
The process-based forest growth model 4C (FORESEE - FORESt Ecosystems in a Changing Environment) was used to analyze the growth of a mixed oak-pine stand [Quercus petraea (Mattuschka) Liebl., Pinus sylvestris L.]. The oak-pine stand is typical for the ongoing forest transformation in the north-eastern lowlands. The pine and the oak trees are 104 and 9 years old, respectively. Three different management scenarios (A, B, C) with different thinning grades and a thinning interval of five years were simulated. Every management scenario was simulated under three different climate scenarios (0K, 2K, 3K) compiled by the regional statistical climate model STAR 2.0 (PIK). For each climate scenario 100 different realisations were generated. The realisations of the climate scenarios encompass the period 2036-2060 and exhibit an increase of mean annual temperature of zero, two and three Kelvin until 2060, respectively. We selected 9 model outputs concerning biomass, growth and harvest which were aggregated to a single total performance index (TPI). The TPI was used to assess the management scenarios with regard to three management objectives (carbon sequestration, intermediate, timber yield) under climate change until 2060. We found out that management scenario A led to the highest TPI concerning the carbon sequestration objective and management scenario C performed best concerning the two other objectives. The analysis of variance in the growth related model outputs showed an increase of climate uncertainty with increasing climate warming. Interestingly, the increase of climate induced uncertainty is much higher from 2 to 3 K than from 0 to 2 K.